BLOCKCHAIN TECHNOLOGY IN MARKETING: EXPLORING DECENTRALIZED SOLUTIONS FOR TRUST AND TRANSPARENCY: LITERATURE REVIEW STUDY - Koko Safitri (CV. Adiba Aisha Amira, 2025)
Blockchain technology has emerged as a disruptive force in marketing, offering decentralized solutions to address trust and transparency issues. This literature review study explores the transformative potential of blockchain in marketing, focusing on its ability to enhance trust, transparency, and operational efficiency. By leveraging blockchain's decentralized ledger system, marketers can combat prevalent challenges such as counterfeit products, data privacy concerns, and opaque supply chains. Key themes identified include the role of blockchain in proof of ownership, transaction validation, brand authentication, and loyalty programs. While blockchain presents opportunities for improving supply chain transparency, enhancing customer loyalty programs, and fostering brand authenticity, challenges such as technical complexity, standardization issues, and implementation costs must be addressed. Future research directions include exploring the long-term impacts of blockchain adoption on marketing practices, quantifying the return on investment of blockchain-based initiatives, and investigating regulatory and ethical implications. Blockchain technology holds immense promise for transforming marketing operations, offering unparalleled trust, transparency, and innovation opportunities.